Investigation of Sexual Function and Its Relationship with Spiritual Health and Religious Attitude in Iranian Women: A Descriptive Study - Zahra Yazdanpanahi; Zahra Beygi; Seyedeh Zohre Sajadian; Zahra Saheb Karam; Mahboubeh Hajifoghaha (Journal of Health Sciences and Surveillance System)
Background: Sexual function is the result of a complex relationship between the body and the mind. It can be affected by various dimensions of health, including spiritual health. In this study, we aimed to assess sexual function and its relationship with spiritual health and religious attitude in Iranian women.Methods: The present descriptive, analytical research was carried out on 514 women in reproductive age, who had referred to the health centers of Shiraz, Iran, from February to September 2015. The participants were required to complete the Religious Attitude Scale, Spirituality Well-being Scale, and Female Sexual Function Index. The psychometric properties of these questionnaires were assessed in Iran. SPSS version 22 was used to analyze the collected data, and a P-value lower than 0.05 was regarded as statistically significant.Results: The mean score of spiritual health was significantly higher in women with a healthy sexual function compared to those with sexual dysfunction (P=0.03). Also, we found a significant relationship between spiritual health and sexual desire (P=0.007) and sexual satisfaction(P=0.03). A significant relationship was also observed between religious health and sexual satisfaction(P=0.03). Besides, the results indicated a significant association between existential health and sexual desire(P=0.002), sexual arousal(P=0.003), and pain(P=0.03). A significant relationship was observed between religious attitude and sexual function(P<0.001).Conclusion: Given that sexual function is one of the basic components of women’s health in reproductive age that needs special attention. It seems that for improving it, taking effective measures such as paying attention to women’s spiritual health can have positive effects on their sexual function.